TRENDS IN ACCOUNTING INFORMATION SYSTEM: OPPORTUNITIES AND CHALLENGES IN MSMES - T K, Dr. Srinath; S, Mrs. Swathi (The journal of contemporary issues in business and government, 2022)
Accounting Information System which integrates the data of all the departments of the company helps decision-makers to take accurate, timely decisions based on the data it collects and stores. Today in this digital era where the majority of the business transactions are happening through digital mode AIS has gained its importance. AIS has immensely contributed to collecting, storing, retrieving, and processing data of the company during pandemics at times where digital means we’re the only path to continue the business. In recent times AIS is becoming one of the tools in improving business efficiency due to its features like quick reporting, integrating data, low cost. In the past 2 decades, AIS has witnessed tremendous technological change. Today digital accounting solutions are experiencing new trends coming up like cloud accounting, artificial intelligence, data analysis, mobile accounting. All businesses are it large or small or micro has to adopt digital accounting solutions to get accurate financial data, faster decision making, easy compliance with the law, good cash flow, business transactions without any obstruction. The review of research done reveals that the contribution towards Indian GDP by MSMEs is increasing year by year. MSMEs in India is contributing around 48% of the country’s exports and will be reaching 60% soon. Though due to pandemics some of the MSMEs were forced to shut down yet they are recovering at a faster pace. Today converting into the digital world has become a necessity for the MSMEs not only to recover but to sustain in the business. This research paper focuses on the recent trends in AIS, opportunities, and challenges faced by MSMEs in adopting digital solutions. MSMEs will be always in a dilemma and find challenging in choosing the traditional accounting method, conventional accounting software, and modern accounting software with the new trends. The research shows that despite having advantages in the adoption of upcoming changes in the field of accounting MSMEs still lag in adopting by facing challenges as to the fulfillment of their day to day requirements.